EFFECTS OF ROSEMARY AND THYME OILS ON SHELF LIFE OF MARINATED SAUCE CRAYFISH - Duman, M.; Coban, O. Emir; Ozpolat, E. (Pakistan Agricultural Scientists Forum, 2015)
The natural preservative effect of rosemary and thyme essential oils on marinated crayfish (Astacus leptodactylus Esch., 1823) stored at 4 degrees C was investigated. Microbiological, chemical and sensory analyses were performed to monitor the changes in quality and to determine the shelf life of marinated crayfish. Microbiological results showed that natural compounds from rosemary and thyme essential oils resulted in lower bacterial growth in marinated crayfish during the chilled storage period. The total volatile basic nitrogen (TVB-N) and the thiobarbituric acid (TBA) values were observed to increase in all groups during the storage period. As for the TBA value, the difference between Group C (Control, without essential oils), Group R (with rosemary oil), and Group T (with thyme oil) was significant (p < 0.05). The shelf life of marinated crayfish was found to be 42 days for Group C, 56 days for Group R, and 70 days for Group T according to the results of sensory and microbiological assessments.
Keywords: Astacus leptodactylus; marination; rosemary oil; thyme oil; shelf life